DARPP-32, a dopamine- and adenosine 3':5'-monophosphate-regulated phosphoprotein: regional, tissue, and phylogenetic distribution - Hemmings, HC (J Neurosci, 1986)
Rabbit antisera and mouse monoclonal antibodies have been prepared to bovine DARPP-32 (dopamine- and adenosine 3':5'-monophosphate-regulated phosphoprotein, Mr = 32,000), and used to study its regional, tissue, and phylogenetic distributions. The antibodies, none of which distinguished between dephospho-DARPP-32 and phospho-DARPP-32, were characterized and used to develop a sensitive and specific radioimmunoassay for DARPP-32. The radioimmunoassay, in conjunction with immunolabeling of SDS/PAGE transfers and immunoprecipitation of phosphorylated tissue extracts, was used to measure immunoreactive DARPP-32 in microdissected regions of rat CNS, in peripheral nervous and non-nervous tissues, and in CNS tissue from various animal species. The distribution of DARPP-32 was generally consistent with the interpretation that it is localized primarily to dopaminoceptive cells that possess dopamine-sensitive adenylate cyclase (D-1 dopamine receptors coupled to adenylate cyclase). Within the rat CNS, DARPP-32 was most highly concentrated in the basal ganglia. DARPP-32 was present in neostriatum from all six mammalian species tested (mouse, rat, guinea pig, rabbit, cow, and rhesus monkey) at concentrations of from 96 to 144 pmol/mg total protein, which constituted from 0.22 to 0.32% of the total protein. DARPP-32 was also identified at low levels in several peripheral tissues, including choroid plexus, parathyroid cells, adrenal chromaffin cells, posterior pituitary gland, pineal gland, and superior cervical sympathetic ganglion. A phylogenetic survey was carried out of proteins immunologically related to DARPP-32 in nervous tissue from nonmammalian species. DARPP-32-like proteins were identified in dopaminoceptive brain regions from representative members of the amniote vertebrate classes (birds and reptiles), while none was identified in dopaminoceptive brain regions from representative members of the anamniote vertebrate classes (bony fishes and amphibians) or in nervous tissue from representative members of several invertebrate classes.